Association between dietary intake and serum biomarkers of long-chain PUFA in Japanese preschool children. Issue 4 (4th March 2021) - Ando, Emiko; Morisaki, Naho; Asakura, Keiko; Ogawa, Kohei; Sasaki, Satoshi; Horikawa, Reiko; Fujiwara, Takeo
Abstract: Objective: Recent research supports the importance of PUFA intake in children, particularly of EPA and DHA; however, few verified methods to assess whether PUFA intake is adequate are available. Design: We assessed the correlation between serum PUFA and lipid concentrations with seafood and PUFA intake measured using a brief-type self-administered diet history questionnaire for Japanese preschool children (BDHQ3y). Setting: Single centre birth cohort in Japan. Participants: A total of 152 36-month-old Japanese children. Results: Average dietary intake of daily seafood, EPA and DHA was 13·83 (sd 10·36) g, 49·4 (sd 43·5) mg and 98·3 (sd 64·6) mg, respectively. Significant weak-to-moderate correlations were observed between dietary intake and serum EPA (Spearman rho = 0·41, P < 0·001; Pearson r = 0·44, P < 0·001); DHA (Spearman rho = 0·40, P < 0·001; Pearson r = 0·42, P < 0·001) and AA (arachidonic acid) (Spearman rho = 0·33, P < 0·001; Pearson r = 0·32, P < 0·001), whereas no significant correlation was observed for dihomo-γ-linolenic acid (DGLA) (Spearman rho = 0·06, P = 0·484; Pearson r = 0·07, P = 0·387). Correlations between seafood intake and serum EPA and DHA were also moderate (0·39–0·43). A negative correlation between serum TAGs and serum EPA, as well as positive correlations between serum cholesterol (total cholesterol, LDL and HDL) with serum EPA and DHA were observed, whereas no significant correlations between seafood intake and serum lipid profiles. Based on this model, we estimated 61–98 g/week of seafood intake is required to meet current EPA/DHA intake recommendations by the WHO (100–150 mg/d). Conclusions: For children of 2–4 years of age, weekly intake of 61–98 g of seafood is required to meet WHO recommendations of EPA/DHA intake.